How circuits work ebook - Roland, James (Connect with Electricity., 2016)
Have you ever wondered how electricity powers your home or school? What about how that electricity travels? In any device that uses electricity, inside is a small path called a circuit through which electricity travels. Whether we see them in these devices or not, circuits are constantly at work. But how do circuits work? How were they invented? Explore the key concepts that make up a circuit, including the power source, conducting path, and load. Learn how circuits power devices of all sizes, from computers to the lights in your home to satellites in outer space!